Barriers and facilitators of cancer genetic risk screening at community-based organizations serving Latinas - Bella Ortega; Maisha R. Huq; Dariana Sedeño-Delgado; Clara Barajas; Sara Gómez-Trillos; Geoffrey Curran; Kristi D. Graves; Vanessa B. Sheppard; Marc D. Schwartz; Beth N. Peshkin; Claudia Campos; Nancy Valencia-Rojas; et al. (Journal of Community Genetics, 2025)
Cancer genetic counseling and testing is potentially lifesaving for individuals at risk of hereditary cancers. Yet, it is severely underutilized among under-resourced Latinas. There has been limited examination of implementing cancer genetic risk screening—the first step of cancer genetic counseling and testing –via community-based organizations (CBOs) serving Latinas. This project explored multilevel barriers and facilitators to implementing cancer genetic risk screening among four CBOs serving Latinas in the Washington DC-Virginia area. We conducted four focus groups with 26 staff at CBOs that implemented a genetic risk screener from January-September 2021. We employed template analysis and a modified Consolidated Framework for Implementation Research (CFIR)—consisting of CFIR’s original five domains ( Process , Intervention , Inner Setting , Outer Setting , Characteristics of Individuals ) and CFIR 2.0’s Adapting construct and a lens emphasizing Health Equity across all domains — to identify barriers and facilitators to implementation. CBOs administered the risk screener to 789 Latinas. A prominent Process barrier was not having the optimal data management system for screening. CBO staff preferred the Intervention (i.e. the screener) over previous family history data collection. Adapting the screener to organizational infrastructure and patient-level health literacy and cultural responsiveness barriers were facilitators. Lack of Inner Setting staff time to conduct screening was a barrier. Stronger systems of CBOs’ Outer Setting partnerships facilitated screening. Characteristics of Individuals that promoted GCT screening was CBO staff knowledge, beliefs, and self-efficacy towards risk screening. Provided that key barriers are addressed and facilitators are leveraged during implementation, genetic risk screening may potentially be feasible and acceptable even across heterogeneous CBOs. Future research evaluating feasibility and acceptability of genetic risk screening in CBOs is needed.